THE CONCEPT OF KHIYAR TA'YIN AND THE RESPONSIBILITY OF BUSINESS ACTORS IN ORDERING FRAMES OF PT GASCO INDAH ACEH, INDONESIA - Asral Miadi; Husni Mubarrak; Wesley Mwafulirwa (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This article aims to discuss the concept of khiyar ta'yin and the responsibility of business actors indering frames at PT Gasco. This type of research is a qualitative descriptive approach through case studies. The main data was obtained from the results of interviews with PT Gasco beautiful pidie district, Indonesia. Meanwhile, secondary data was obtained from a number of articles related to this study. The results of the study show that first, PT Gasco indah did not see a grace period for buying and selling frames. Hanafiyah scholars mentioned three conditions for the validity of khiyar ta'yin, namely the choice for made for similar goods of different quality and nature, the goods have different property and values, and the grace period for khiyar ta'yin must be determined. Second, the form of responsibility has been regulated in article 28 of law No.8 of 1999, for the truth that business actors have caused consumer losses which essentially states that the burden and responsibility of business actors in providing compensation can be in the form of refunds, replacement of goods and services of the same or equivalent value, health care and the provision of compensation.